Single-cell analysis of long non-coding RNAs in the developing human neocortex. Issue 1 (December 2016) - Liu, Siyuan; Nowakowski, Tomasz; Pollen, Alex; Lui, Jan; Horlbeck, Max; Attenello, Frank; He, Daniel; Weissman, Jonathan; Kriegstein, Arnold; Diaz, Aaron; Lim, Daniel
Abstract Background Long non-coding RNAs (lncRNAs) comprise a diverse class of transcripts that can regulate molecular and cellular processes in brain development and disease. LncRNAs exhibit cell type- and tissue-specific expression, but little is known about the expression and function of lncRNAs in the developing human brain. Furthermore, it has been unclear whether lncRNAs are highly expressed in subsets of cells within tissues, despite appearing lowly expressed in bulk populations. Results We use strand-specific RNA-seq to deeply profile lncRNAs from polyadenylated and total RNA obtained from human neocortex at different stages of development, and we apply this reference to analyze the transcriptomes of single cells. While lncRNAs are generally detected at low levels in bulk tissues, single-cell transcriptomics of hundreds of neocortex cells reveal that many lncRNAs are abundantly expressed in individual cells and are cell type-specific. Notably, LOC646329 is a lncRNA enriched in single radial glia cells but is detected at low abundance in tissues. CRISPRi knockdown ofLOC646329 indicates that this lncRNA regulates cell proliferation. Conclusion The discrete and abundant expression of lncRNAs among individual cells has important implications for both their biological function and utility for distinguishing neural cell types.